Testing a Biological Weapon Detection System in a Distributed Virtual Reality Environment - Beckman, Paul (International Journal of Virtual Reality, 2001)
A study called Bio-Sim was sponsored by the U.S. Army to examine the LR-BSDS (Long-Range Biological Standoff Detection System), a laser-based biological cloud detector. Testing of the device was performed in a distributed virtual reality environment (DVRE). The three primary objectives of the study were to: 1) determine appropriate tactics, techniques, and procedures for use of the LR-BSDS, 2) gain a better understanding of those battlefield situations and characteristics that limit the effective use of the LR-BSDS, and 3) demonstrate the potential to use a DVRE simulation for training using the LR-BSDS. This paper will focus on the third of those objectives. The study consisted of three phases. The first phase involved calculating theoretical concentration limits of a dispersed biohazard as a function of time, dispersion concentration, and distance to sensor. The second phase resulted in a set of abbreviated bio-cloud detection missions run in a DVRE. The third phase was a set of full-length human-in-the-loop trial missions run by trained LR-BSDS operators and helicopter flight crews, using a DVRE and computer-based simulators for the LR-BSDS, helicopter, biocloud dispersion, and bio-cloud transport.